Arabic Dialects of Lamomea and Pudahoa at Students in Gontor 4 and 7 Southeast Sulawesi - Laode Abdul Wahab; Aris Try Andreas Putra Putra (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: The symptom of using two languages in the local dialect of the Arabic speaking community in Southeast Sulawesi can be seen as an interesting phenomenon. This study aims to identify and reveal: (1) The Arabic language of local dialect â€œPudahoaâ€ at Pondok Putra 7 and â€œLamomeaâ€ at Gontor Putri 4 in Southeast Sulawesi; (2) Coding variations in the communication of Arabic language in the local dialects of Lamomea and Pudahoa; and (3) the use of local Arabic dialects of Lamomea and Pudahoa. Methodology: This research was conducted in the speaking community of Southeast Sulawesi who uses the local Arabic dialect located in Konawe Selatan at two focuses: (1) Arabic Lamomea; and (2) Arabic Pudahoa speaking community. The method used in this research is descriptive method qualitative. The descriptive method is an attempted research method to describe and interpret objects according to the circumstances. Findings: This study found: first, the Arabic variation used in social interactions in Gontor Putri 4 is Arabic in the Lamomea dialect. Meanwhile, the Arabic variation used in social interactions in Gontor Putri 7 is Arabic in the Pudahoa dialect. The variations of code-switching that occur in the speech communities of Gontor Putri 4 and Gontor Putra 7 with the linguistic repertoire that exists in the community include first, code-switching in the form of language translation and second, code-switching in the form of speech level code-switching. Furthermore, the codes found in Arabic spoken by the Gontor Putri 4 and Putra 7 speaking community are in the form of phrases. Mix this code in the form of an Indonesian phrase into a sentence or speech. Lamomea and Pudahoa dialect Arabic as a subordinate standard language have several functions. Third, the use of Arabic in the local dialects of Lamomea and Pudahoa consists of the formal domain, kinship domain, religious domain, transactional use, social environment, informal environment, and non-formal domain. Conclusion: There are variations of code-switching, and code-mixing in the Arabic speech communities of Lamomea and Pudahoa, Tthe Lamomea and Pudahoa dialects have local and regional characteristics and functions as a means of internal communication, a symbol of community identity and as a means of communication in formal, informal and non-formal situations. The author hopes that there will be further research that focuses on how patterns of influence between Arabic and local culture. Keywords: Arabic language form; coding variations; the dialect use.